(untitled) (Africa Development, 2021)
Contents Editorial: International Criminal Justice, Peace and Reconciliation in Africa – The ICC and Beyond Ato Kwamena Onoma.................................1 The International Criminal Court, Justice, Peace and the Fight against Impunity in Africa: An Overview André Mbata Mangu.................................7 The ICC, International Criminal Justice and International Politics Henrietta J.A.N. Mensa-Bonsu......................33 Between Tunnel Vision and a Sliding Scale: Power, Normativity and Justice in the Praxis of the International Criminal Court Obiora Chinedu Okafor & Uchechukwu Ngwaba......55 Ensuring Peace and Reconciliation while Holding Leaders Accountable: The Politics of ICC Cases in Kenya and Sudan Tim Murithi ................................73 Intricate Entanglement: The ICC and the Pursuit of Peace, Reconciliation and Justice in Libya, Guinea, and Mali Siba N. Grovogui..................................99 The Justice versus Reconciliation Dichotomy in the Struggle Against Gross Human Rights Violations: The Nigerian Experience Idayat Hassan & Benson Olugbuo................123 Perceptions de la « justice des vainqueurs » : engagements de la CPI et processus de paix et de réconciliation en Ouganda, en République démocratique du Congo et en Côte d’Ivoire Jean-Pierre Fofé Djofia Malewa..............143 Prosecuting International Crimes in Africa: Lessons from Rwanda and Reflections on the Future Hassan B. Jallow ............................. 177 The Case for a Modest Assessment of the International Criminal Justice Processes in Rwanda and Sierra Leone and some Lessons for Liberia Charles Chernor Jalloh & Andrew Morgan ............ 191 International Criminal Justice, Peace and Reconciliation in Africa: Re-imagining an Agenda Beyond the ICC Chidi Anselm Odinkalu........................ 257